A randomized comparison of the laryngeal mask airway supreme™ and laryngeal mask airway unique™ in infants and children: does cuff pressure influence leak pressure?. Issue 10 (23rd March 2013) - Jagannathan, Narasimhan; Sohn, Lisa; Sommers, Katherine; Belvis, Dawn; Shah, Ravi D.; Sawardekar, Amod; Eidem, Jami; DaGraca, Justin; Mukherji, Isabella; Anderson, Brian
Summary Background The cuff pressure for optimal airway sealing with first‐generation laryngeal mask airway has been shown to be 40 cm H2O in children. Currently, there are no data regarding the ideal intracuff pressure for the laryngeal mask airway Supreme (Supreme) in children. Objectives To compare the clinical performance of the laryngeal mask airway supreme with the laryngeal mask airway unique in infants and children. Materials and methods One hundred eighty children were assigned to receive either a Supreme or a laryngeal mask airway‐U. We hypothesized higher airway leak pressure with the Supreme at both 40 cm H2O and 60 cm H2O, when compared with the laryngeal mask airway‐U. Ease and time of insertion, insertion attempts, fiber optic examination, quality of airway, efficacy of mechanical ventilation, success of gastric tube placement (Supreme), incidence of gastric insufflation, and complications were also assessed. Results Airway leak pressure at an intracuff pressure of 60 cm H2O for the Supreme was 17.4 (5.2) vs laryngeal mask airway‐U at 18.4 (6.6) cm H2O and did not differ when compared to an intracuff pressure of 40 cm H2O for both devices; Supreme at 17.2 (5) vs laryngeal mask airway‐U at 17.7 (6) cm H2O. The laryngeal mask airway‐U was associated with higher first‐attempt success rates. The Supreme was associated with less gastric insufflation than the laryngeal mask airway‐U. Conclusions Intracuff pressures of 40 cm H2O may be sufficient for the Supreme in children, and there may be no added benefit of an intracuff pressure of 60 cm H2O, as leak pressures were similar. The Supreme may be preferred over the laryngeal mask airway‐U for its lower rates of gastric insufflation and provision for gastric access when mechanical ventilation is utilized.